Polydopamine‐Modified Black Phosphorous Nanocapsule with Enhanced Stability and Photothermal Performance for Tumor Multimodal Treatments. Issue 10 (16th August 2018) - Zeng, Xiaowei; Luo, Miaomiao; Liu, Gan; Wang, Xusheng; Tao, Wei; Lin, Yaoxin; Ji, Xiaoyuan; Nie, Lin; Mei, Lin
Abstract: As a novel 2D material, black phosphorus (BP) nanosheets are considered as a promising candidate for drug delivery platform for synergistic chemo/photothermal therapy. However, the intrinsic instability of bare BP poses a challenge in its biomedical applications. To date, some strategies have been employed to prevent BP from rapid ambient degradation. Unfortunately, most of these strategies are not suitable for the drug delivery systems. Here, a simple polydopamine modification method is developed to enhance the stability and photothermal performance of bare BP nanosheets. Then, this nanocapsule is used as a multifunctional codelivery system for the targeted chemo, gene, and photothermal therapy against multidrug‐resistant cancer. The enhanced tumor therapy effect is demonstrated by both in vitro and in vivo studies. Abstract : A simple polydopamine modification method is developed to enhance the stability and photothermal performance of bare black phosphorus nanosheets. Then, this nanocapsule is used as a multifunctional codelivery system for the targeted chemo, gene, and photothermal therapy against multidrug‐resistant cancer. The enhanced tumor therapy effect is demonstrated by both in vitro and in vivo studies.